Head-to-head comparison of CAMPYAIR aerobic culture medium versus standard microaerophilic culture for Campylobacter isolation from clinical samples - Levican, Arturo; Varela, Carmen; Porte, Lorena; Weitzel, Thomas; Briceño, Isabel; Guerra, Francisco; Mena, Benjamín; Hinton, Arthur (Frontiers in Cellular and Infection Microbiology, 2023)
Campylobacter spp. are considered the most frequent cause of acute gastroenteritis worldwide. However, outside high-income countries, its burden is poorly understood. Limited published data suggest that Campylobacter prevalence in low- and middle-income countries is high, but their reservoirs and age distribution are different. Culturing Campylobacter is expensive due to laboratory equipment and supplies needed to grow the bacterium (e.g., selective culture media, microaerophilic atmosphere, and a 42°C incubator). These requirements limit the diagnostic capacity of clinical laboratories in many resource-poor regions, leading to significant underdiagnosis and underreporting of isolation of the pathogen. CAMPYAIR, a newly developed selective differential medium, permits Campylobacter isolation without the need for microaerophilic incubation. The medium is supplemented with antibiotics to allow Campylobacter isolation in complex matrices such as human feces. The present study aims to evaluate the ability of the medium to recover Campylobacter from routine clinical samples. A total of 191 human stool samples were used to compare the ability of CAMPYAIR (aerobic incubation) and a commercial Campylobacter medium (CASA, microaerophilic incubation) to recover Campylobacter. All Campylobacter isolates were then identified by MALDI-TOF MS. CAMPYAIR showed sensitivity and specificity values of 87.5% (95% CI 47.4%–99.7%) and 100% (95% CI 98%–100%), respectively. The positive predictive value of CAMPYAIR was 100% and its negative predictive value was 99.5% (95% CI 96.7%–99.9%); Kappa Cohen coefficient was 0.93 (95% CI 0.79–1.0). The high diagnostic performance and low technical requirements of the CAMPYAIR medium could permit Campylobacter culture in countries with limited resources.